To find the value of \( x \) in the problem involving two adjacent angles that sum up to 90 degrees, we can set up the equation:
\[ x + (x + 30) = 90 \]
Now, combine like terms:
\[ 2x + 30 = 90 \]
Next, subtract 30 from both sides:
\[ 2x = 90 - 30 \] \[ 2x = 60 \]
Now, divide both sides by 2:
\[ x = \frac{60}{2} \] \[ x = 30 \]
So, the value of \( x \) is \( 30 \) degrees.
To find the measure of the second angle, we can calculate \( x + 30 \):
\[ x + 30 = 30 + 30 = 60 \]
Therefore, the two angles are \( 30 \) degrees and \( 60 \) degrees, and they sum to \( 90 \) degrees, confirming our solution.